A Critical Introduction to "Massive Open Online Courses (MOOCs)" - Masoumeh Matoor; Khadijeh Aliabadi; Naser Mozayani; Ali Delavar; Mohammad Reza Nili Ahmadabadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present study aims at introducing and criticizing the mass open online courses (MOOCs). To this end, the "Critical Philosophical Exploration" method was used. The statistical population comprised all books, articles, studies, and research pertaining to the subject that was selected with purposive sampling and the maximum probable sources. The data required were collected through notetaking which were analyzed by verbal, visual and logical inference. In this paper, MOOCs was first described in three axes: "what", "why", and "how"; then, to interpret MOOCs, the criteria (a) underlying theory, (b) educational justice, (c) adult education, (d) practicality in technical terms, and (e) the educational applications were selected and the MOOCs were analyzed and finally, their advantages and disadvantages were summarized. According to the findings of this article, MOOC's most important benefits included: advanced scientific underlying theory, laying the groundwork for educational justice, proportionality with adult education, operational capability, and various educational advantages and advantages. However, the new underlying theory of MOOCs (relativism) and its many criticizes, MOOCs ability to create and spread educational discrimination, various technical shortcomings, and serious deficiencies in educational application were among the disadvantages. Consequently, dealing with MOOCs needs awareness of these advantages and disadvantages and attempts to resolve them.